Proteins involved in carbon metabolism induce bleomycin resistance - Burgos-Molina, Antonio Manuel; Alamilla Presuel, Juan Carlos; Mercado-Sáenz, Silvia; González Vidal, Alejandro; Ruiz González, Óscar M.; Ruiz-Gómez, Miguel José (Aseica, 2022)
S. cerevisiae acquires bleomycin resistance after a long-term exposure to this drug which causes overexpression of TPIS protein. It could be involved in the resistance process. For this reason, it could be good candidates as bleomycin chemo-resistance biomarker. Knowing of the homologous gene in humans facilitates more studies of the expression of this protein in tumors.
Keywords: Proteínas - Análisis - Congresos; Proteins; Carbon metabolism; Bleomycin resistance